Characterization of passive layers formed on Ti–10 wt% (Ag, Au, Pd, or Pt) binary alloys and their effects on galvanic corrosion. (July 2015) - Hwang, Moon-Jin; Park, Eun-Jin; Moon, Won-Jin; Song, Ho-Jun; Park, Yeong-Joon
Highlights: Ti alloys containing 10 wt% Ag, Au, Pd, or Pt element were prepared. The properties of passive layers were investigated by electrochemical method. The stratified four layers were formed on Ti alloys. Each layer effected on the properties of the adjacent layers. The outer layer played an important role on the initial galvanic corrosion. Abstract: Ti binary alloys containing 10 wt% noble metal elements of Ag, Au, Pd, or Pt were prepared to obtain the different phase structures. The metallurgical phase structures and corrosion behavior of Ti alloys were investigated. From the ac impedance data analysis, the passivation model on Ti alloys was established and electrochemical parameters of stratified layers were obtained. The stratified layers successively consisted of the metal defect, inner, intermediate, and outer layers on the surface of Ti alloys. The properties of outer layer played an important role on the initial galvanic corrosion.